2015
DOI: 10.1177/0194599815578104
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Detection of Parotid Gland Malignancy during Primary Extracapsular Dissection

Abstract: Objective. To evaluate the oncologic and functional outcome in cases in which a false preoperative working hypothesis ''benign parotid tumor'' led to a primary extracapsular dissection being performed rather than a traditional, more radical surgical modality.Study Design. Case series with chart review.Setting. Academic tertiary referral center.Subjects and Methods. The records of all patients treated for malignant tumors of the parotid gland between 2006 and 2012 were retrospectively studied. Patients were exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…Although there was no difference in 10‐year disease‐specific survival, this study was not powered to demonstrate noninferiority between the treatment methods. Mantsopoulos et al reported 29 patients who underwent extracapsular dissection in unexpected parotid tumors. Five‐year OS was 100% and local disease control was 96.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was no difference in 10‐year disease‐specific survival, this study was not powered to demonstrate noninferiority between the treatment methods. Mantsopoulos et al reported 29 patients who underwent extracapsular dissection in unexpected parotid tumors. Five‐year OS was 100% and local disease control was 96.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in preoperative evaluation and diagnostic sensitivity of FNA may lead to encountering malignancy intraoperatively when benign pathology was anticipated. In cases in which the index of suspicion is low for malignancy, patients may receive more conservative surgery compared to the extent of dissection required for known malignancy . Two small case series consisting of patients with unexpected parotid gland malignancies demonstrated that more conservative surgery may be adequate .…”
Section: Introductionmentioning
confidence: 99%
“…A final potential argument against extracapsular dissection is that it might have an adverse effect on the course of cases in which definitive histology reveals unexpected malignancy. A study of the relevant literature shows that unexpected malignancy on definitive histology after minimal invasive surgical modalities (extracapsular dissection) on the parotid gland appears in 3.4% to 4.8% of cases . Interestingly, a literature report of the same working group demonstrated consistently acceptable functional and oncologic results after primary extracapsular dissection in such cases .…”
Section: Discussionmentioning
confidence: 99%
“…Extracapsular dissection was defined as meticulous dissection around the tumor capsule and tumor extirpation with a layer of healthy tissue without the intention to preidentify or expose the main trunk or branches of the facial nerves . This modality was indicated in solitary and mobile tumors located within the lateral lobe of the parotid gland with preoperative clinical and imaging signs of benign tumor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation